Influence of Antipsychotic Drug Risperidone on Human Serum Albumin Affinity to Organic Anions - Syrejshchikova, Tatiana; Smolina, Natalia; Kondratyuk, Valentin; Dobretsov, Gennady; Uzbekov, Marat (Current Drug Discovery Technologies, 2018)
Background: Risperidone is an antipsychotic drug. In blood, this drug binds mainly to human serum albumin (HSA) and is also transported by HSA. Method: To study certain details of the interaction between risperidone and HSA, a fluorescent dye CAPIDAN was used as a reporter. This dye specifically fluoresces from HSA in serum and is highly sensitive to structural changes in HSA including pathology-induced changes. Interaction of CAPIDAN with HSA has been studied using time-resolved fluorescence techniques. Result: The addition of phenylbutazone, a marker for the HSA drug-binding site I, leads to displacement of CAPIDAN from this site due to direct competition between phenylbutazone and the dye. The addition of risperidone induces a response of CAPIDAN fluorescence that is highly similar to its response to phenylbutazone. This response depends strongly on ionic strength and is very similar in both cases, phenylbutazone and risperidone. This similarity suggests that risperidone binds to HSA in the region of site I. In this site, the risperidone molecule probably covers the positive charge of Arginine 218 or Arginine 222 preventing their interaction with the CAPIDAN negatively charged carboxyl group. This effect was observed both in isolated HSA and in serum, suggesting similarity of the interaction. Conclusion: Thus, risperidone is able to prevent binding of organic anions (i.e. CAPIDAN as a drug-like molecule) to HSA.
Keywords: property of site I